Avian influenza - Ebtsam M El-Kady; Hanaa A El- Shafei; SoadA Saleh (Journal of Vaccines and Immunology - Peertechz Publications, 2019)
Infl uenza A H5N1 subtype known as avian fl u is an emerging and extremely contagious virulent disease that poses a risk to the international community's security.In latest years, by establishing itself as a important emerging infectious disease, it has become a major public health issue. It is one of more than 25 infl uenza A viruses that mainly live in all bird species [1]. It has been noted that migratory birds can play a part in avian infl uenza virus transmission, blacktailed gull and chickens infection with avian infl uenza (H13N2) and (H13N8) viruses in eastern China. They discovered these H13 viruses transmitted to national poultry from migratory birds.